2016
DOI: 10.1080/14756366.2016.1217857
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the transmembrane carbonic anhydrase isoforms IX and XII in the inflamed synovium

Abstract: Juvenile idiopathic arthritis (JIA) is the most common form of chronic rheumatic disease affecting children worldwide, with some features similar to adult rheumatoid arthritis (RA). In the present study, we aim at investigating novel markers that will allow in the future for tailored, more personalized treatment strategies. Hence, taking notice of several reports proving the role of local acidosis as a causal link between inflammatory diseases and related pain, and the involvement of several carbonic anhydrase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 12 publications
(14 reference statements)
0
64
1
Order By: Relevance
“…112 Recently, overexpression of isoforms IX and XII has been also detected in patients affected by juvenile idiopathic arthritis (JIA), which is considered as the most common form of RA in pediatric patients. 113 In vitro studies revealed that CA I significantly promote CaCO 3 formation besides enhancing hydration reaction. Calcium salt precipitation is a key step of bone formation and CA I play an important role in this key step.…”
Section: Ra and Osteoporosismentioning
confidence: 99%
“…112 Recently, overexpression of isoforms IX and XII has been also detected in patients affected by juvenile idiopathic arthritis (JIA), which is considered as the most common form of RA in pediatric patients. 113 In vitro studies revealed that CA I significantly promote CaCO 3 formation besides enhancing hydration reaction. Calcium salt precipitation is a key step of bone formation and CA I play an important role in this key step.…”
Section: Ra and Osteoporosismentioning
confidence: 99%
“…Many such enzymes from vertebrates, protozoa, fungi, and bacteria are well-known drug targets 1–13 , and their inhibitors possess pharmacologic applications, being clinically used for the management of glaucoma 1 , 14 , edema 1 , 15 , obesity 16 , epilepsy 17 , hypoxic tumors 1 , 2 , 18 , 19 , idiopathic intracranial hypertension 20 , etc. Ultimately, some human (h) CA isoforms have also been validated as drug targets for cerebral ischemia 21 , neuropathic pain 22 , and arthritis 23 , whereas many such enzymes present in pathogenic organisms may lead to the development of anti-infectives with a new mechanism of action 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently Margheri et al . reported that CA IX and XII are overexpressed in the synovial fluid of patients with juvenile idiopathic arthritis, whereas in normal controls this overexpression does not occur.…”
Section: Therapeutic Applications Of Carbonic Anhydrase IX Inhibitorsmentioning
confidence: 99%
“…Recently Margheri et al 288 reported that CA IX and XII are overexpressed in the synovial fluid of patients with juvenile idiopathic arthritis, whereas in normal controls this overexpression does not occur. This was the starting point for investigating whether inhibition of CA IX (and XII) in animal models of arthritis may be a useful and innovative approach for the pharmacological intervention.…”
Section: Antiarthritis Agentsmentioning
confidence: 99%